Al Fatawa al kubra - Ibn-Taymiyyah (Dar al Kutub al 'Ilmiyyah ; Dar al Ma'rifah; Maktabah al Mathna, 1987)
ws.jl.1,3,4-5.c.1-3,jl.3,4.c.5-6,jl.6.c.1,jl.2.c.5/ stc14=jl.2. c.7/stc13,jil.3,c.6; jil.4,c.6